(untitled) (Papeles, 2022)
Humans —along with other categories of subjects such as legal subjects or ideal existence— are subjects of rights and the legislation in Argentina establishes and endorses it. Now, when we shift to the animal side, the situation is different. The Argentinian law, animals are taken as things and, consequently, there is no recognition that provides them the quality of subjects of rights. Which is why this generates a series of debates that, on the one hand, question the current legislation and, on the other hand, seek for groundings that foster recognition of non,human animals. These debates are inserted not only in the doctrine, but also in the jurisprudence. This latter one produces greater interpretations and adaptations on whether the current law tries to justify favourable decisions on the rights of animals. Therefore, this work will analyze the recognition of the condition of subject rights towards animals from recent cases of jurisprudence so as to value the tenets used in these final judgments to sentence in favour or not.